Coaching and Mentoring: how to develop Top talent and Achieve stronger performance (Boston : Harvard Business School, 2004)
Business
2011-11-17
Keywords: Mentoring and Coaching; Mentoring; Coaching; Mentoring and Management; Women and Minorities